1982
DOI: 10.1002/abio.370020203
|View full text |Cite
|
Sign up to set email alerts
|

Regulation der mikrobiellen Alkanoxidation mit Hinblick auf die Produktbildung

Abstract: Catabolic pathways of long‐chain n‐alkanes in the range of C8 to C18 are demonstrated and results of investigation about the regulation of monoterminal oxidation are given: – Enzymes of monoterminal alkane oxidation usually are inducible – Several intermediates of alkane oxidation can inhibit the primary oxidation of concerned alkane –Substances, e.g. glucose and glycerol, which ordinary don't be developed in catabolic alkane reactions, in many cases have an inhibitory effect on alkane oxidation The regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For example, Rehm & Reiff (1982) investigated the initial mode of attack on C8 to C18 n-alkanes by a variety of bacteria and fungi. Most organisms brought about terminal oxidation only but with certain Aspergillus, Fusarium and Bacillus spp.…”
Section: Metabolism Of N-alkanesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Rehm & Reiff (1982) investigated the initial mode of attack on C8 to C18 n-alkanes by a variety of bacteria and fungi. Most organisms brought about terminal oxidation only but with certain Aspergillus, Fusarium and Bacillus spp.…”
Section: Metabolism Of N-alkanesmentioning
confidence: 99%
“…Woods & Murrell (1989) have reported that the propane-oxidising bacterium Rhodococcus rhodochrous can produce monoterminal and diterminal oxidation of C2-Cs n-alkanes via a system that is not linked to cytochrome P-450. In a survey of n-alkane oxidation in a number of microbial species, Rehm & Reiff (1982) observed diterminal oxidation products only rarely. All of these products may be further metabolized by means of the []-oxidation pathway for fatty acids.…”
Section: Metabolism Of N-alkanesmentioning
confidence: 99%
“…Alkanes and fatty acids are oxidized via subterminal, terminal or diterminal oxidation [17][18][19][20][21]. Subterminal oxidation is described for Aspergillus sp., Fusarium spp.…”
Section: Oxidation Mechanismsmentioning
confidence: 99%
“…and Bacillus spp. and represents the oxidation of subterminal carbon atoms in the alkanes or fatty acids [19]. Terminal and diterminal oxidation is described in different yeast species e.g., Candida tropicalis, C. maltosa and Yarrowia lipolytica and represents the oxidation of terminal methyl groups of alkanes or fatty acids [21,22].…”
Section: Oxidation Mechanismsmentioning
confidence: 99%